2018
DOI: 10.21873/anticanres.12810
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Volume and Intramuscular Adipose Tissue Are Prognostic Predictors of Postoperative Complications After Hepatic Resection

Abstract: Intensive surgical care is necessary for high-risk patients with hemodialysis, psychiatric disorder, high CONUT count and/or low skeletal muscle quality to reduce postoperative complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…The development of ascites in patients with HCC is associated with various factors, including malnutrition (8) The controlling nutritional status (CONUT) score is a nutritional index consisting of three parameters: Serum albumin level, total cholesterol level, and lymphocyte count (9) CONUT is superior than other nutritional assessment tools such as the Nutrition Risk Screening-2002 and subjective global assessment to predict infectious complication in patients with digestive diseases (10). In addition, the CONUT score was reported to predict the development of ascites in patients with HCC (11) While, intramuscular adipose tissue (IMAT) content is a method for the quantification of fatty infiltration in skeletal muscles (12) IMAT is reported to be an independent risk factor for mortality in patients with HCC (13) IMAT was also reported to be significantly associated with liver dysfunction and the prognosis of HCC patients who underwent hepatectomy (14).…”
Section: Introductionmentioning
confidence: 99%
“…The development of ascites in patients with HCC is associated with various factors, including malnutrition (8) The controlling nutritional status (CONUT) score is a nutritional index consisting of three parameters: Serum albumin level, total cholesterol level, and lymphocyte count (9) CONUT is superior than other nutritional assessment tools such as the Nutrition Risk Screening-2002 and subjective global assessment to predict infectious complication in patients with digestive diseases (10). In addition, the CONUT score was reported to predict the development of ascites in patients with HCC (11) While, intramuscular adipose tissue (IMAT) content is a method for the quantification of fatty infiltration in skeletal muscles (12) IMAT is reported to be an independent risk factor for mortality in patients with HCC (13) IMAT was also reported to be significantly associated with liver dysfunction and the prognosis of HCC patients who underwent hepatectomy (14).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that sarcopenia and visceral adiposity, as a more and more closely watched predictor, play important roles in nutritional assessment, which has been proven to be related to postoperative complications in various diseases including gastric cancer, hepatocellular carcinoma (HCC), pancreatic cancer, and endometrial cancer (38)(39)(40)(41)(42). However, the impacts of preoperative sarcopenia, muscle steatosis, and visceral adiposity on short-term outcomes after liver resection for HAE remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal muscle quality, visceral fat mass, and skeletal muscle mass were measured on preoperative CT images using the graphic analysis software Ziostation (ZIOSOFT). For muscle quality, CT values (Hounsfield units: HUs) of the regions of interest were measured at the umbilical level, and the intramuscular adipose tissue content (IMAC) was calculated by dividing the CT value of the multifidus muscles by that of subcutaneous fat, as in previous studies 18‐22 . Visceral fat area (VFA), defined as HUs of −150 to −50, was measured at the umbilical level and skeletal muscle, defined as HUs of −29 to 150, at the level of the third lumbar vertebra.…”
Section: Methodsmentioning
confidence: 99%
“…The European Working Group on Sarcopenia in Older People revised its guidelines in 2018 and included reduced skeletal muscle quality in addition to reduced quantity to confirm the diagnosis of sarcopenia 15 . Recently, studies have been published linking poor skeletal muscle quality to postoperative complications in patients with gynecologic cancer, 16 colorectal cancer, 17 and hepatocellular carcinoma 18,19 . The relationship between muscle quality and postoperative complications in patients with gastric cancer is inadequately studied.…”
Section: Introductionmentioning
confidence: 99%